Mentalități și modele de consum în perioada de tranziție la economia de piață - Stanciu, Mariana (Calitatea Vieții, 1994)
The author tries to interpret the results of some interviews carried out in September-October 1992 on two groups of subjects collected on demo-social and economic criteria from both urban and rural. The questions focused on the patterns of food-consumption, consumption of public services and family budget. There have been also analyzed the opinions concerning the relation between work time and leisure time face with the '80s.